UPAYA MENINGKATKAN HASIL BELAJAR IPS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE (STAD) - Rosmita, Rosmita; Achmadi, Achmadi; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Â AbstractThis study aimed to improve social studies learning outcomes by using cooperative type Student Team Achievement Devisions (STAD) in Eighth Grade at SMP Negeri 4 Teriak Bengkayang. The sub-problem in this study is